2000
DOI: 10.1143/jjap.39.2321
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Single-Electron Transistor (SET) Model for Design and Analysis of Realistic SET Circuits

Abstract: In this work, we propose a compact, physically based, analytical single-electron transistor (SET) model suitable for the design and analysis of realistic SET circuits. The model is derived on the basis of the “orthodox” theory of correlated single-electron tunneling and the steady-state master equation method. The SET inverter characteristics are successfully calculated using the model implemented in the simulation program with integrated circuit emphasis (SPICE). The hybrid circuit of SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 9 publications
0
53
0
1
Order By: Relevance
“…However, they are too slow for analysis of large circuits. Uchida et al proposed an analytical SET model and incorporated it into SPICE [23]. Recently, Inokawa et al extended this model to a more general form to include asymmetric SETs [24].…”
Section: A Past Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are too slow for analysis of large circuits. Uchida et al proposed an analytical SET model and incorporated it into SPICE [23]. Recently, Inokawa et al extended this model to a more general form to include asymmetric SETs [24].…”
Section: A Past Workmentioning
confidence: 99%
“…Researchers have reported device operation at each level but the 40k B T requirement is more reliable. At charging energies over 10k B T , the model we use is accurate to within 4% of the time-dependent master equation [23,38].…”
Section: ) Junction Resistancementioning
confidence: 99%
“…We explicitly consider the effects of thermal noise; they are reflected in our design decisions and their impacts on power consumption and performance are considered. At charging energies over ½¼ Ì , the model we use is accurate to within 4% of the time-dependent master equation [14,18].…”
Section: Iiia5) Reliability Implicationsmentioning
confidence: 99%
“…SIMON [12] and MOSES [13] are the two most popular SET simulators which, nevertheless, are not suitable for circuit analysis due to large runtimes when characterizing systems containing more than a few SETs. Uchida et al proposed an analytical SET model and incorporated it into SPICE [14]. Recently, Inokawa et al extended this model to a more general form to include asymmetric SETs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only two compact analytical models (Uchida et al, for single gate resistive symmetric SET [1] and Mahapatra et al, for asymmetric SET [2]) have been reported. We propose an improved model, which is more flexible and can be adapted for symmetrical and asymmetrical device geometries.…”
Section: Introductionmentioning
confidence: 99%